Strategic Management of Sustainable Development of Romania in the European Context – Europe 2020 - Cristina COTOCEL; Bogdan GRIGORAŞ; Constantin FLOREA; Nicolae CONCIOIU; Adrian STAN (Revista de Management Comparat International)
This article is an analysis of how the overall Romania targets relate to EU development strategy Europe 2020 on each of the five major objectives set by the European Commission. The main objective of this document is to study development indicators presented by our country by 2013 compared to those assumed by the other EU countries. Based on this analysis and Relating to the observations and recommendations made by the EU for 2015 will pursue active management plans to achieve the 2020 targets set by Romania on the five major objectives of development. According to data available on 15 March 2014 and presented in the National Reform Programme 2014 of the Government Romania's chances to reach the targets are quite low, reducing the difference between the current and proposed situation may be possible through the development of a management focused on strategic diagnostics of each target both internally and externally its environment .